A Latent Structure Analysis of Cognitive Vulnerability to Depression in Adolescence. Issue 4 (July 2019) - Liu, Richard T.; McArthur, Brae Anne; Burke, Taylor A.; Hamilton, Jessica L.; Mac Giollabhui, Naoise; Stange, Jonathan P.; Hamlat, Elissa J.; Abramson, Lyn Y.; Alloy, Lauren B.
Abstract: Whether cognitive vulnerability to depression exists along a continuum of severity or as a qualitatively discrete phenomenological entity has direct bearing on theoretical formulations of risk for depression and clinical risk assessment. This question is of particular relevance to adolescence, given that cognitive vulnerability appears to coalesce and rates of depression begin to rise markedly during this period of development. Although a dimensional view is often assumed, it is necessary to submit this assumption to direct empirical evaluation. Taxometric analysis is a family of statistical techniques developed directly to test such assumptions. The present study applied taxometric methods to address this question in a community sample of early adolescents ( n = 485), drawing on three indices of cognitive vulnerability to depression (i.e., negative inferential style, ruminative response style, self-referent information processing). The results of three taxometric analyses (i.e., mean above minus below a cut [MAMBAC], maximum eigenvalue [MAXEIG], and latent mode [L-Mode]) were consistent in unambiguously supporting a dimensional conceptualization of this construct. The latent structure of the tested indices of cognitive vulnerability to depression in adolescence appears to exist along a continuum of severity rather than as a discrete clinical entity. Highlights: Cognitive vulnerability features prominently in theories of depression Cognitive vulnerability to depression is commonly assumed to be dimensional This requires direct empirical evaluation and has etiological and clinical importance This is the first taxometric study of cognitive vulnerability to depression in youth Consistent evidence of dimensionality was observed